Targeting NUFIP1 Suppresses Growth and Induces Senescence of Colorectal Cancer Cells - Shen, Aling; Wu, Meizhu; Liu, Liya; Chen, Youqin; Chen, Xiaoping; Zhuang, Mingkai; Xie, Qiurong; Cheng, Ying; Li, Jiapeng; Shen, Zhiqing; Wei, Lihui; Chu, Jianfeng; et al. (Frontiers in Oncology, 2021)
Abstract NUFIP1 is an RNA-binding protein that interacts with fragile X mental retardation protein (FMRP) in the messenger ribonucleoprotein particle (mRNP). We previously showed that NUFIP1 was upregulated in colorectal cancer (CRC), but how the protein may contribute to the disease and patient prognosis is unknown. Here we combine database analysis, microarray, quantitative PCR, and immunohistochemistry of patients' samples to confirm our previous findings on NUFIP1 overexpression in CRC, and to reveal that increased expression of NUFIP1 in CRC tissues correlated with worse overall, recurrence-free, event-free and disease-free survival in patients, as well as with more advanced CRC clinicopathological stage. Loss of function analysis demonstrated that NUFIP1 knockdown suppressed cell growth in vitro and in vivo, inhibited cell viability and survival, and induced cell cycle arrest and apoptosis in vitro, as well as up-regulated Bax and down-regulated Bcl-2 protein expression. In addition, as a natural anticancer triterpene from various fruits and vegetables, ursolic acid (UA) treatment suppressed cell proliferation, down-regulated NUFIP1 protein expression, and further enhanced the effects of NUFIP1 knockdown in CRC cells in vitro. NUFIP1 knockdown up-regulated the expression of 136 proteins, down-regulated the expression of 41 proteins, and enriched multiple signaling pathways including the senescence-associated heterochromatin foci (SAHF) pathway. Furthermore, NUFIP1 knockdown enhanced the expression of senescence-associated-β-galactosidase (SA-β-gal), the SAHF markers HP1γ and trimethylation (H3k9me3), and the senescence-related protein HMGA2, as well as both p53 and its downstream p21 protein expression. Our findings suggest that NUFIP1 is overexpressed in CRC and correlates with disease progression and poor patient survival. NUFIP1 may exert oncogenic effects partly by altering senescence. UA may show potential to treat CRC by down-regulating NUFIP1.